Dreams Content and Emotional Load in Cardiac Rehabilitation Patients and Their Relation to Anxiety and Depression - Komasi, Saeid (Ann Card Anaesth, 2018)
BACKGROUND: The assessment of a dream and its mechanisms and functions may help us to percept cognitions, emotions, and complex behaviors of patients. Hence, the present study aimed to assess (i) the rate of perceived dream and its emotional load and content and (ii) the relationship between functions of dream with anxiety and depression. METHODS: In this cross-sectional study, 167 cardiac patients who had undergone rehabilitation in the western part of Iran were assessed during May–October 2016. Research instrument included Beck depression inventory, Beck anxiety inventory, Schredl's dream emotions manual, and content analysis of dreams manual. The findings were analyzed through Pearson's correlative coefficient and multiple regression analysis. RESULTS: The mean age of participants (66.5% men) was 59.1 ± 9 years. The results indicated that the emotional content of patients’ dreams included happiness (49.1%), distress (43.1%), sad (13.8%), fear (13.2%), and anger (3%). Although women report more sad dreams than men (P = 0.026), there was no difference between them in terms of other components of dreams, anxiety, and depression. Regression models showed that anxiety and depression were significantly able to predict perceived dream rates (P = 0.030) and emotionally negative dreams (P = 0.019). CONCLUSION: The increased rates of depression, especially anxiety, are related to increasing perceived dreams with negative and harmful emotional load. Regarding severity and negative content of dreams are reflexes of stressful emotional daily experiences, the management of experienced psychological symptoms such as depression and anxiety is concerned as an undeniable necessity.